2020
DOI: 10.1101/2020.04.28.064113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational design of protein-specific folding modifiers

Abstract: 16Protein folding can go wrong in vivo and in vitro, with significant consequences for the living cell and 17 the pharmaceutical industry, respectively. Here we propose a general design principle for constructing 18 small peptide-based protein-specific folding modifiers. We construct a 'xenonucleus', which is a pre-19folded peptide that resembles the folding nucleus of a protein, and demonstrate its activity on the 20 folding of ubiquitin. Using stopped-flow kinetics, NMR spectroscopy, Förster Resonance Energy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 99 publications
(1 reference statement)
4
11
0
Order By: Relevance
“…For example, ceftriaxone binds specifically to the C-terminal region of the intrinsically disordered protein α-synuclein, generally understood to be involved in triggering Parkinson’s disease, and has shown therapeutic potential. Also, recent experimental results suggest that the folding kinetics of proteins with two-state transitions can be modulated by the employment of suitable peptides that mimic specific segments of the protein chain . Although the purpose of the experiment was the opposite of the one sought for here, as the goal was to speed up the folding transition, the results provide general support for the contention presented that specific peptide molecules can interfere and alter the folding kinetics of globular proteins.…”
Section: Discussion: a Possible Avenue To Protein Folding-interdictin...supporting
confidence: 51%
See 1 more Smart Citation
“…For example, ceftriaxone binds specifically to the C-terminal region of the intrinsically disordered protein α-synuclein, generally understood to be involved in triggering Parkinson’s disease, and has shown therapeutic potential. Also, recent experimental results suggest that the folding kinetics of proteins with two-state transitions can be modulated by the employment of suitable peptides that mimic specific segments of the protein chain . Although the purpose of the experiment was the opposite of the one sought for here, as the goal was to speed up the folding transition, the results provide general support for the contention presented that specific peptide molecules can interfere and alter the folding kinetics of globular proteins.…”
Section: Discussion: a Possible Avenue To Protein Folding-interdictin...supporting
confidence: 51%
“…Also, recent experimental results suggest that the folding kinetics of proteins with two-state transitions can be modulated by the employment of suitable peptides that mimic specific segments of the protein chain. 64 Although the purpose of the experiment was the opposite of the one sought for here, as the goal was to speed up the folding transition, the results provide general support for the contention presented that specific peptide molecules can interfere and alter the folding kinetics of globular proteins. The proposed therapeutic strategy is depicted in Figure 2 .…”
Section: Discussion: a Possible Avenue To Protein Folding-interdictinmentioning
confidence: 67%
“…The concepts presented in this paper are similar to earlier proposals to develop drugs that might be therapeutic by interfering with the folding process [21,22]. There has been a growing interest in the possibility of modulating the folding process through the employment of specific molecules, and theoretical and experimental results have been recently reported that support the view that targeting folding dynamics is a promising path for therapeutic development [23][24][25]. The main difference between the proposal presented here and other approaches is that the FITR strategy aims to interdict in the folding process while the protein is still completely unfolded [13].…”
Section: Introductionsupporting
confidence: 59%
“…By altering the length, attachment point, and chemical nature of the stapling agents, the design of stapled peptides can be tuned to achieve desirable affinity and target specificity. 18,24,25 Few experimental and computational reports have checked the stability of stapled ACE2 and their binding with RBD. 21,26,27 However, a rationale to combine stapling agents chemical nature and length with their binding affinity is still lacking which is crucial for the future design of stapled peptides.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of stapling agents to positions 28, 32, 36, and 40 improves the binding considerably. In the case of ACE2_al-al, the fluctuation of the N-terminal end of the peptide(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) has significantly decreased compared to ACE2_wt though the C-terminal end(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) shows deviation from strong association with RBD surface (Movie S2). This has been reflected in the RMSF (Figure5C) and fraction helicity (Figure6C) as well.…”
mentioning
confidence: 99%